The Prognostic Significance of Revised 'Post-Cardiac Arrest Syndrome for Therapeutic Hypothermia' Score on Neurological Outcomes in Post-cardiac Arrest Patients - Altuntas, Gulsum; Berilgen, Emine Busra; Demirel, Oguzhan (Springernature, 2025)
Background and PurposeRisk scoring is necessary for managing post-cardiac arrest patients. We aimed to calculate revised 'Post-Cardiac Arrest Syndrome for Therapeutic Hypothermia'(rCAST) scores in Post-Cardiac Arrest Patients (PCAS) who underwent therapeutic temperature management (TTM) and to evaluate the rCAST score in predicting the 30-day CPC of PCAS patients (CPC 1: Full recovery, CPC 2: Moderate disability, CPC 3: Severe disability, CPC 4: Coma or vegetative state, CPC 5: Death).MethodsIt is a retrospective single-centre observational study. PCAS patients over 18 who were admitted to the 3rd Step ICUs between January 2018 and May 2024 and who underwent TTM were searched from their files and hospital electronic database. Primary endpoint: To evaluate the significance of the rCAST score in predicting the 30-day Cerebral Performance Category (CPC) of PCAS patients, Secondary endpoint: To evaluate the significance of the rCAST score in predicting 30-day mortality. To measure the predictive value of rCAST value for CPC and mortality, Youden Index Receiver operating characteristic (ROC) curves were plotted and the Area Under the Curve (AUC) was determined. Logistic regression analysis was performed to estimate the CPC and mortality. For mortality and neurologic outcome calibration analysis was performed.ResultsOf 237 postcardiac arrest patients, 158 received TTM treatment, and 96 met the inclusion criteria. The AUC of the rCAST score for mortality is 0.82, and for CPC is 0.90. In the logistic regression for poor neurological outcome (CPC >= 3), the rCAST score was found to be a statistically significant independent risk factor, with an odds ratio (OR) of 2.333 (95% CI 1.215-4.483, p = 0.011). Calibration analysis demonstrated good agreement between predicted and observed outcomes for both mortality (Hosmer-Lemeshow p = 0.761) and CPC >= 3 (Hosmer-Lemeshow p = 0.339).ConclusionDespite the neuroprotective effects of TTM, patients with high rCAST scores still face significant risks for poor neurological outcomes. The rCAST score may be a valuable tool for the early identification of high-risk patients who may benefit from follow-up and adjunctive therapies aimed at neurological improvement.
Keywords: rCAST score; Post cardiac arrest; Targeted temperature management; Neuroprognosis; Mortality